Advanced techniques for detecting vitamin D, phosphorus, and calcium in rohu (labeo rohita) - Sarwar, Aqsa; Al-Sulivany, Basim. S. A.; Owais, Muhammad; Abbas, Ghulam; Altaf, Javaria; Hassan, Syed Sibt E (International Journal of Aquatic Research and Environmental Studies, 2025)
The objective of this study was to establish the serum levels of Vitamin D, calcium (Ca2+), and phosphorus (P) in Labeo rohita under controlled laboratory environments, which would help in establishing the relationship between them and how this would affect the physiology of the fish. The specimens of the Young Labeo rohita were kept in the experimental tanks, and they were fed on a diet of 30 percent crude protein. A Vitamin D concentration in blood serum, a calcium concentration in blood serum, and a phosphorus concentration in blood serum were determined using High-performance liquid chromatography (HPLC) to measure Vitamin D concentration, colorimetric analysis to measure calcium concentration, and Enzyme-linked immunosorbent assays (ELISA) to measure phosphorus concentration in the blood serum. The findings revealed that the average blood Vitamin D level was 515.0 + ± 63.15 ng/mL and the range was between 79.1 and 1071.0 ng/mL. The mean serum calcium level was 10.35 + ± 1.37 mg/dl with a range of 7.99-12.27 mg/dl. The average value of phosphorus was 15.75 + ± 1.3 mg/dL, with a range of 7.54-34.56 mg/dL. Also, considerable correlations were found to exist between shifts in the levels of Vitamin D and the phosphorus and calcium levels. These results highlight the importance of Vitamin D in keeping the mineral balance in the physiology of fish. The interdependence of these nutrients that has been measured implies that their concentration depends on several conditions, such as diet and environment. More studies should be carried out to ensure that feed formulations are used according to the nutritional requirements of various fish species, which are favorable practices in the commercial fish farming industry.